Identification, distribution, and hosts of Meloidogyne spp. infecting horticultural crops in Florida, USA with focus on Meloidogyne enterolobii - Riva Gabrieli; Brito Janete A.; de Oliveira Clemen; Marin Marcus; Gu Mengyi; Bui Hung Xuan; Desaeger Johan (Journal of Nematology)
Many root-knot nematode (RKN) species in the genus Meloidogyne occur in Florida, including M. enterolobii, a species able to overcome RKN resistance genes in many crops. The distribution of these nematodes in horticultural crops is not well known. A RKN survey was conducted in South and Central Florida aiming to: (i) identify RKN infecting vegetables, fruit, and other crops; (ii) document host plants; (iii) determine RKN distribution; and (iv) gain insight on the relatedness of M. enterolobii obtained in this study with other populations from the USA and other countries. A total of 304 soil and root samples were collected from 56 plant species cultivated in commercial vegetable and fruit farms, research farms, horticultural gardens, Asian vegetable farms, and natural landscapes in 12 counties. Meloidogyne species identification was performed using mitochondrial haplotype-based identification, species-specific primers, DNA sequencing and phylogenetic analysis. RKN were detected in 247 out of 304 (81.25%) root samples collected from September 2019 to January 2023. Five RKN species (M. arenaria, M. enterolobii, M. hapla, M. incognita and M. javanica) were identified. The most prevalent RKN were M. incognita and M. enterolobii, which were found in 25% of the samples. Less prevalent were M. javanica, found in 16%, and M. arenaria and M. hapla, found in 8% and 5% of samples, respectively. Mixed populations of M. enterolobii and M. incognita were found in 1% of the samples. Phylogenetic analysis showed low genetic variability among DNA sequences of M. enterolobii populations from Florida, other states in the USA, and other countries. New host records found in this study include: a worldwide host record, Solanum capsicoides (M. enterolobii); new US continental host records, Vigna unguiculata (M. enterolobii), Opuntia cochenillifera (mixed species – M. enterolobii and M. incognita). Additionally, new state host records found were Cannabis sativa, Colocasia esculenta, and Lilium sp. (M. arenaria), Phaseolus vulgaris (M. enterolobii), Cucumis melo (M. hapla), and Lavandula angustifolia and Helianthus annuus (M. incognita). These findings confirm the predominance of tropical RKN species, and especially of M. enterolobii, in Florida. and provide new insights into the distribution, prevalence, and hosts of RKN species in horticultural crops in Central and South Florida.